DEVELOPMENT OF STUDENT WORKSHEETS BASED ON CONTEXTUAL TEACHING AND LEARNING IN SCIENCE LEARNING - Sulistyowati Sulistyowati; Nur Inayah Syar (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2021)
AbstractThis research was conducted based on the results of observations made by researchers when teaching science courses to prospective MI/SD teacher students. The main problem faced by students is the difficulties in presenting the science concept from textbooks or modules, learning media (videos and PowerPoint slides), and virtual laboratories into real-life contexts. Students also have difficulty learning independently and are less active in the learning process. The purpose of this research is to develop Student Worksheets (LKM) based on Contextual Teaching and Learning in Science Studies and Learning courses. The research method used was Research and Development (R&D). The development design used in this research was ADDIE. The results showed that the CTL-based Student Worksheet Development (LKM) was developed using the ADDIE design which includes analysis stage (needs and curriculum analysis), the design stage (combining LKM components with CTL stages), the development stage (making instruments and feasibility test), implementation stage (distribution of LKM to determine the students' perceptions) and evaluation stage (final stage revision of LKM). Based on the results of the feasibility test, the LKM is in the